1996
DOI: 10.1128/aem.62.10.3673-3678.1996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation in freshwater: Escherichia coli is able to develop natural competence

Abstract: Until now, Escherichia coli was thought to be unable to develop natural competence, i.e., genetic transformation could be achieved only artificially with the aid of nonphysiological concentrations of calcium ions or by other treatments. We have tested the competence development of E. coli through transformation under natural conditions in river water, springwater, and mineral water which contained between 0 and 11 mM Ca 2؉ , using pUC18 DNA. The presence of calcium ions at concentrations as low as 1 to 2 mM wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(72 citation statements)
references
References 47 publications
3
65
1
3
Order By: Relevance
“…Many previous reports of bacterial gene transfer in biofilms have described conjugation (Davey & O'Toole, 2000;Roberts et al, 2001;Bushman, 2002;Molin & Tolker-Nielsen, 2003;Sorensen et al, 2005), and several others reported in situ transformation among naturally transformable bacteria (Stewart et al, 1983;Wang et al, 2002;Hendrickx et al, 2003). Although natural transformation of E. coli by artificially added DNA was reported in several experimental systems (Baur et al, 1996;Bauer et al, 1999;Tsen et al, 2002;Woegerbauer et al, 2002;Maeda et al, 2003Maeda et al, , 2004, our result provides the first evidence that the nonconjugative nonviral DNA can be horizontally transmitted between E. coli cells. This result challenges conventional bacterial genetics.…”
Section: Plasmid Transfer In Colony Biofilm Vs In Liquid Culturessupporting
confidence: 56%
See 1 more Smart Citation
“…Many previous reports of bacterial gene transfer in biofilms have described conjugation (Davey & O'Toole, 2000;Roberts et al, 2001;Bushman, 2002;Molin & Tolker-Nielsen, 2003;Sorensen et al, 2005), and several others reported in situ transformation among naturally transformable bacteria (Stewart et al, 1983;Wang et al, 2002;Hendrickx et al, 2003). Although natural transformation of E. coli by artificially added DNA was reported in several experimental systems (Baur et al, 1996;Bauer et al, 1999;Tsen et al, 2002;Woegerbauer et al, 2002;Maeda et al, 2003Maeda et al, , 2004, our result provides the first evidence that the nonconjugative nonviral DNA can be horizontally transmitted between E. coli cells. This result challenges conventional bacterial genetics.…”
Section: Plasmid Transfer In Colony Biofilm Vs In Liquid Culturessupporting
confidence: 56%
“…Escherichia coli is not thought to be naturally transformable; it develops high genetic competence only under artificial conditions, such as exposure to high Ca 21 concentrations (Mandel & Higa, 1970). However, recently, several reports showed that E. coli can express modest genetic competence under certain conditions possible in its environments (Baur et al, 1996;Bauer et al, 1999;Tsen et al, 2002;Woegerbauer et al, 2002;Maeda et al, 2003). We recently revealed that E. coli cells within a colony biofilm developed modest genetic competence under Ca 21 -poor conditions, such as growth and incubation on Luria-Bertani (LB) agar (Maeda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…E. coli populations are known to increase rapidly under conditions of fasting [19]. Furthermore, E. coli can be induced to take up DNA and is known to develop natural competence under certain conditions [20].…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, artificial transformation by the calcium chloride (CaCl 2 ) [9,10] or other methods [11,12] is well known as a common laboratory technique, but natural transformation is poorly understood. Several reports [13][14][15][16][17][18] including ours [19][20][21] demonstrated that E. coli can develop modest genetic competence for transformation under conditions occurring in usual natural and human environments.…”
Section: Introductionmentioning
confidence: 95%